Perspektif Hukum Medical Tourism di Indonesia: Prospek dan Tantangan - Felasufa Noor (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
It is estimated that the medical tourism industry in Asia will be worth US4 billion by 2022, and Indonesia is positioning itself as one of the main players in the region, expecting revenues of up to US590 million in five years. In 2022 alone, Indonesia received 341,288 medical tourists with an income of 253.84 million. Thus, the potential of this industry is very large, and the Indonesian government is taking the right strategic steps in this direction. Medical tourism as it is currently practiced and promoted is a relatively new concept, although patients traveling long distances to seek medical care is nothing new. This journal explores the development and growth of medical tourism in a global context, as well as among key Asian players in the industry, before turning to the Indonesian experience. The role of key players in advancing the industry agenda, namely the Ministry of Health, Ministry of Tourism, Ministry of International Trade and Industry, Association of Private Hospitals etc., will also be discussed. Finally, the challenges faced by an industry that is still in its infancy will also be discussed.